Disaster Resilient Cities: Concepts and Practical Examples - 360391 Hayashi, Yoshitsugu; Hayashi, Yoshitsugu, 1951- editor; Suzuki, Yasuhiro, 1961-; 1958- editor; Tsukahara, Kenichi, editor (Boston, MA : Elsevier, 2016)
Includes bibliographical and references